2014
DOI: 10.1155/2014/930894
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Rich Saline Inhibits NLRP3 Inflammasome Activation and Attenuates Experimental Acute Pancreatitis in Mice

Abstract: Increasing evidence has demonstrated that reactive oxygen species (ROS) induces oxidative stress and plays a crucial role in the pathogenesis of acute pancreatitis (AP). Hydrogen-rich saline (HRS), a well-known ROS scavenger, has been shown to possess therapeutic benefit on AP in many animal experiments. Recent findings have indicated that the NOD-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome, an intracellular multiprotein complex required for the maturation of interleukin- (IL-) 1β, may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…As an important component of the innate immune system, the NLRP3 inflammasome could be activated by endogenous molecules known as damage-associated molecular patterns (DAMPs), such as DNA, adenosine triphosphate (ATP), high mobility group box 1 (HMGB1), and nucleotide binding oligomerization domain 2 (NOD2) which are all associated with inflammation during the development of pancreatitis. Furthermore, components of the inflammasome, specifically ASC, caspase-1, and NLRP3, are required for the development of inflammation in acute pancreatitis85758. Taken together with our results, these findings suggest that TSG-6 can act as an antagonist of the NLRP3 inflammasome, resulting in attenuation of cellular inflammatory processes and consequent relief of pancreatic injury during SAP.…”
Section: Discussionsupporting
confidence: 78%
“…As an important component of the innate immune system, the NLRP3 inflammasome could be activated by endogenous molecules known as damage-associated molecular patterns (DAMPs), such as DNA, adenosine triphosphate (ATP), high mobility group box 1 (HMGB1), and nucleotide binding oligomerization domain 2 (NOD2) which are all associated with inflammation during the development of pancreatitis. Furthermore, components of the inflammasome, specifically ASC, caspase-1, and NLRP3, are required for the development of inflammation in acute pancreatitis85758. Taken together with our results, these findings suggest that TSG-6 can act as an antagonist of the NLRP3 inflammasome, resulting in attenuation of cellular inflammatory processes and consequent relief of pancreatic injury during SAP.…”
Section: Discussionsupporting
confidence: 78%
“…Reduction of oxidative stress by the antioxidant hydrogen suppressed activation of NLRP3 inflammasome and maturation of IL-1 β that have deepened current understanding of antioxidants in managing AP [12]. Our data revealed that NLRP3 inflammasome activation is associated with cerulein-induced inflammation in acini and suppressed by SFN.…”
Section: Discussionmentioning
confidence: 57%
“…Also, oxidative stress contributes to not only the amplification of pancreatic damage but also the progression of local inflammation to systemic inflammatory responses [6]. Therefore, supplementation with exogenous antioxidants represents a beneficial therapeutic strategy or a useful adjunctive option in the treatment of AP [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies focusing on the neuroprotective effects of HS in other nerve injury models, such as focal ischemia and reperfusion [53], Parkinson's disease [54], brain &p<0.05 vs. SAH group; &&p<0.01 vs. SAH group; @ p<0.05 vs. SAH+vehicle group; @@ p<0.01 vs. SAH+vehicle group stem infarct [55], intracerebral hemorrhage [56], neonatal hypoxia-ischemia [57], traumatic brain injury [58], spinal cord injury [59], et al, and numerous articles demonstrated that HSinduced beneficial effect is partially involved of NF-κB pathway [60][61][62]53]. As a well-established representative of inflammation, NF-κB has been reported to be activated after SAH [63][64][65].…”
Section: Discussionmentioning
confidence: 99%